2014
DOI: 10.1016/j.devcel.2014.07.021
|View full text |Cite
|
Sign up to set email alerts
|

Trim58 Degrades Dynein and Regulates Terminal Erythropoiesis

Abstract: SUMMARY TRIM58 is an E3 ubiquitin ligase superfamily member implicated by genome wide association studies (GWAS) to regulate human erythrocyte traits. Here we show that Trim58 expression is induced during late erythropoiesis and that its depletion by shRNAs inhibits the maturation of late stage nucleated erythroblasts to anucleate reticulocytes. Imaging flow cytometry studies demonstrate that Trim58 regulates polarization and/or extrusion of erythroblast nuclei. In vitro, Trim58 directly binds and ubiquitinate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
71
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(79 citation statements)
references
References 67 publications
3
71
1
Order By: Relevance
“…Fortunately, advances in both sequencing technology and functional approaches have allowed for the direct study of human erythropoiesis and disorders due to alterations of this process. GWAS coupled with thorough functional follow-up have identified novel roles for BCL11A as an essential HbF silencing factor (Sankaran et al, 2008), CCND3 and CCNA2 as regulators of RBC size and number (Ludwig et al, 2015; Sankaran et al, 2012a), TRIM58 as a regulator of enucleation (Thom et al, 2014), and SMIM1 as a key RBC surface protein encoding the Vel blood antigen (Cvejic et al, 2013). Studies of rare genetic disorders in humans have revealed novel, and sometimes unexpected, findings, such as an erythroid-specific defect due to ribosomal protein haploinsufficiency in Diamond Blackfan anaemia (Ludwig et al, 2014).…”
Section: Model Systems and Organisms Used For Understanding Erythropomentioning
confidence: 99%
“…Fortunately, advances in both sequencing technology and functional approaches have allowed for the direct study of human erythropoiesis and disorders due to alterations of this process. GWAS coupled with thorough functional follow-up have identified novel roles for BCL11A as an essential HbF silencing factor (Sankaran et al, 2008), CCND3 and CCNA2 as regulators of RBC size and number (Ludwig et al, 2015; Sankaran et al, 2012a), TRIM58 as a regulator of enucleation (Thom et al, 2014), and SMIM1 as a key RBC surface protein encoding the Vel blood antigen (Cvejic et al, 2013). Studies of rare genetic disorders in humans have revealed novel, and sometimes unexpected, findings, such as an erythroid-specific defect due to ribosomal protein haploinsufficiency in Diamond Blackfan anaemia (Ludwig et al, 2014).…”
Section: Model Systems and Organisms Used For Understanding Erythropomentioning
confidence: 99%
“…The TRIM proteins frequently possess E3 ubiquitin ligase activities and participate in a broad range of physiological processes and disease, including innate immunity, development process, genetic diseases, and cancer (11). It has been reported that TRIM58 regulated terminal erythroid cell cycles and enucleation (12). However, the association between TRIM58 and HCC has not been well documented.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, circulating RBCs at this developmental stage are a mixture of primitive yolk sac-derived and definitive aorta-gonad-mesonephros (AGM)-derived cells (45). In contrast, the assays of erythroid cell enucleation we employ, similar to those used by many other groups (31,(46)(47)(48), utilize bone marrow-and fetal liver-derived hematopoietic progenitors, both of which are definitive AGM-derived cells. Importantly, in both sets of assays ( Fig.…”
Section: Discussionmentioning
confidence: 98%